Assessment of the relationship between vitamin D levels and uterine fibroids in Turkish women: A retrospective case–control study - Ferhat Çetin; Özer Birge; İlkan Kayar (Journal of International Medical Research)
Objective Uterine fibroids are prevalent in women of reproductive age and can cause various health issues. This study aimed to explore the association between vitamin D levels and the development of uterine fibroids in Turkish women, a topic on which contradictory findings have been reported. Methods This retrospective case–control study was conducted at Osmaniye State Hospital, Turkey, from September 2022 to September 2023. The study group comprised women diagnosed with uterine fibroids, while the control group included women who did not have uterine fibroids. Both groups were compared based on their vitamin D levels, sociodemographic characteristics, obstetric health, clinical characteristics, and imaging findings. The primary focus of the study was on the correlation between vitamin D levels and the presence of uterine fibroids. Results The study group involved 954 women with uterine fibroids, and the control group comprised 668 control women. The sociodemographic characteristics of the groups were not significantly different (p > 0.05). However, the median vitamin D level in the study group (9.9 ng/mL) was significantly lower than that in the control group (16.1 ng/mL, p < 0.001). Furthermore, patients with multiple uterine fibroids had significantly lower vitamin D levels than those with a single fibroid (p = 0.032). Women with three or more fibroids had even lower levels of vitamin D than those with fewer than three fibroids (p < 0.001). Conclusion The findings indicate a marked association between lower vitamin D levels and the presence of uterine fibroids. Patients with a higher number of fibroids had lower vitamin D levels. These results suggest a potential link between vitamin D deficiency and the development of uterine fibroids. However, more prospective studies are required to determine the exact role of vitamin D in the development and progression of uterine fibroids.